Polo-Like Kinase 2: From Principle to Practice - Zhang, Chuanyong; Ni, Chuangye; Lu, Hao (Frontiers in Oncology, 2022)
Polo-like kinase (PLK) 2 is an evolutionarily conserved serine/threonine kinase that shares the n-terminal kinase catalytic domain and the C-terminal Polo Box Domain (PBD) with other members of the PLKs family. In the last two decades, mounting studies have focused on this and tried to clarify its role in many aspects. PLK2 is essential for mitotic centriole replication and meiotic chromatin pairing, synapsis, and crossing-over in the cell cycle; Loss of PLK2 function results in cell cycle disorders and developmental retardation. PLK2 is also involved in regulating cell differentiation and maintaining neural homeostasis. In the process of various stimuli-induced stress, including oxidative and endoplasmic reticulum, PLK2 may promote survival or apoptosis depending on the intensity of stimulation and the degree of cell damage. However, the role of PLK2 in immunity to viral infection has been studied far less than that of other family members. Because PLK2 is extensively and deeply involved in normal physiological functions and pathophysiological mechanisms of cells, its role in diseases is increasingly being paid attention to. The effect of PLK2 in inhibiting hematological tumors and fibrotic diseases, as well as participating in neurodegenerative diseases, has been gradually recognized. However, the research results in solid organ tumors show contradictory results. In addition, preliminary studies using PLK2 as a disease predictor and therapeutic target have yielded some exciting and promising results. More research will help people better understand PLK2 from principle to practice.